Compression-sensitive smart windows: inclined pores for dynamic transparency changes - Haomin Chen; Gunho Chang; Tae Hee Lee; Seokhwan Min; Sanghyeon Nam; Donghwi Cho; Kwonhwan Ko; Gwangmin Bae; Yoonseong Lee; Jirou Feng; Heng Zhang; Jang-Kyo Kim; et al. (Nature Communications, 2024)
Abstract Smart windows, capable of tailoring light transmission, can significantly reduce energy consumption in building services. While mechano-responsive windows activated by strains are promising candidates, they face long-lasting challenges in which the space for the light scatterer’s operation has to be enlarged along with the window size, undermining the practicality. Recent attempts to tackle this challenge inevitably generate side effects with compromised performance in light modulation. Here, we introduce a cuttlefish-inspired design to enable the closing and opening of pores within the 3D porous structure by through-thickness compression, offering opacity and transparency upon release and compression. By changing the activation mode from the conventional in-plane to through-thickness direction, the space requirement is intrinsically decoupled from the lateral size of the scatterer. Central to our design is the asymmetry of pore orientation in the 3D porous structure. These inclined pores against the normal direction increase the opaqueness upon release and improve light modulation sensitivity to compression, enabling transmittance regulation upon compression by an infinitesimal displacement of 50 μm. This work establishes a milestone for smart window technologies and will drive advancements in the development of opto-electric devices.